1D Cole-Cole inversion of TEM transients influenced by induced polarization - Seidel, Marc; Tezkan, Buelent (ELSEVIER, 2017)
Effects of induced polarization (IP) can have an impact on time-domain electromagnetic measurements (TEM) and may lead to sign reversals in the recorded transients. To study these IP effects on TEM data, a new 1D inversion algorithm was developed for both, the central -loop and the separate-loop TEM configurations using the Cole-Cole relaxation model. ID forward calculations for a homogeneous half-space were conducted with the aim of analyzing the impacts of the Cole-Cole parameters on TEM transients with respect to possible sign reversals. The forward modelings showed that the variation of different parameters have comparable effects on the TEM transients. This leads to an increasing number of equivalent models as a result of inversion calculations. Subsequently, 1D inversions of synthetic data were performed to study the potentials and limitations of the algorithm regarding the resolution of the Cole-Cole parameters. In order to achieve optimal inversion results, it was essential to error-weight the data points in the direct vicinity of sign reversals. The obtained findings were eventually adopted on the inversion of real field data which contained considerable IP signatures such as sign reversals. One field data set was recorded at the Nakyn kimberlite field in Western Yakutiya, Russia, in the central loop configuration. Another field data set originates from a waste site in Cologne, Germany, and was measured utilizing the separate -loop configuration. (C) 2017 Elsevier B.V. All rights reserved.